Republic of Belarus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper reviews developments during 2001-02 in the Belarusian pension system, and discusses potential short- and medium-term reforms needed to put pension system finances on a sustainable path. The paper presents a short overview of demographic trends and developments in Belarus and their impact on the pension system. It discusses the financial difficulties of early 2002 and the policy measures the authorities took to deal with them. A critical review of the methodology used in preparing annual Social Protection Fund budgets is also presented.